Wage-based Dowry Legal Paradigm: Perspectives of Muslim Generation Z in Surabaya - Hadi, Mukhammad Nur; Syatta, Indy Mafiiqo; Safitri, Eka; Sabri, Fahruddin Ali; Masum, Ahmad (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
This paper traces the perception of Generation Z Muslims in Surabaya about marriage dowry. Data was obtained from questionnaires distributed to them, and finally received 174 respondents. Two things that were tracked were their perception of the Regional Minimum Wage-based dowry quality and quantity standards and their legal paradigm towards the idea of wage-based dowry. This study shows two important things. First, most of them disagree with wage-based dowry in the context of quantity. On the other hand, in the context of quality, they agree that dowry should be of productive value. At this point, they display a unique position because productivity is interpreted dually, wage-based standards and not. Second, they respond to this issue using four paradigms: sociological, normative, anthropological, and juridical. Sociological and juridical paradigms create the value of reciprocal protection, male and female. The normative paradigm establishes the importance of patriarchal protection. While the anthropological paradigm is more binding on the preservation of tradition. Here, it can be seen that the paradigm influence of protection on women in the context of wage-based dowry standards is quite strong, although sometimes women are trapped in a patriarchal paradigm.